Factors Determining Parental Attitudes Towards Termination of Pregnancy in Prenatally Detected Down Syndrome - Ömer Talip Turhan; Mehmet Serdar Kütük; Ruksan Büyükoğlan; Mehmet Dolanbay; Mahmut Tuncay Özgün; Özlem Turhan; Mürşide Şahin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aims of this study are to explore the rate of termination of pregnancy for Down syndrome in Turkey and to investigate demographic characteristics of the parents that may influence the parents' decision. STUDY DESIGN: The study was conducted in Erciyes University, Department of Obstetrics and Gynecology, Prenatal Diagnosis Unite between 2009-2011. The data of 58 fetuses prenatally diagnosed as Down syndrome were analyzed retrospectively. The effects of socio- demographic features, obstetric history and educational level on termination of pregnancy for Down syndrome were compared retrospectively. RESULTS: The mean maternal age was 33.3±7.2 years. There were no statistically significant correlation between the termination rate and any of the socio- demographic features. In case of reproductive history, the termination rate was significantly higher in women who had at least one living child than women who had no child. Contrary to our expectations, termination rate was higher in patients from rural area than in patients from urban center (p <0.05). CONCLUSION: Majority of parents choose to terminate pregnancy when the fetus diagnosed as Down syndrome. Our findings indicate that if parents have reasonable understanding of raising a child, they are most likely to terminate their pregnancy in the case of Down syndrome.